2010
DOI: 10.1007/s00709-010-0128-6
|View full text |Cite
|
Sign up to set email alerts
|

Do Cecidomyiidae galls of Aspidosperma spruceanum (Apocynaceae) fit the pre-established cytological and histochemical patterns?

Abstract: Cecidomyiidae galls commonly present a zonation of tissues with lignified cell layers externally limiting a reserve tissue and internally limiting a specialized nutritive tissue next to the larval chamber. The cytological aspects of this specialized tissue indicate high metabolic activity as well as carbohydrate accumulation. In Aspidosperma spruceanum-Cecidomyiidae gall system, ultrastructural and histochemical investigations corroborated this pattern and also revealed the storage of proteins in the nutritive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 36 publications
3
42
0
8
Order By: Relevance
“…The formation of a suberized covering in galls was already observed in other systems such as Guarea macrophylla subsp. tuberculata (Meliaceae)-Cecidomyiidae [7] and Copaifera langsdorffii (Leguminosae)-Cecidomyiidae [8,18]. The thickness of the cuticle, trichomes neoformation, and the eventual substitution of epidermis for periderm are characters that reinforce the hypothesis of the microenvironment [3,49], which benefits gall inducing herbivores.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The formation of a suberized covering in galls was already observed in other systems such as Guarea macrophylla subsp. tuberculata (Meliaceae)-Cecidomyiidae [7] and Copaifera langsdorffii (Leguminosae)-Cecidomyiidae [8,18]. The thickness of the cuticle, trichomes neoformation, and the eventual substitution of epidermis for periderm are characters that reinforce the hypothesis of the microenvironment [3,49], which benefits gall inducing herbivores.…”
Section: Discussionmentioning
confidence: 57%
“…During gall formation, several alterations in epidermis, parenchyma, xylem and phloem cells take place [6]. Also, periderm and new vascular bundles differentiation [7][8][9], cuticle thickness, increase in number of non glandular trichomes, crystals and sclereids appearance, changes in mesophyll cell shapes [7,[10][11][12][13][14], and the formation of a nutritive tissue [7,[15][16][17][18][19] are some of the most common alterations observed during the development of gall structure.…”
Section: Introductionmentioning
confidence: 99%
“…This accumulation of ROS occurred in the cells of non-galled tissues, which are the mother cells of the gall parenchymatic cortex in Aspidosperma australe and A. spruceanum [75,76]. Agrawal (2006) suggested that the unbalancing of ROS and antioxidant production is evidence of oxidative stress.…”
Section: Evidence Of Ros Accumulation and Redox Imbalance During Gallmentioning
confidence: 96%
“…High concentrations of ROS in gall tissues were detected via the 3.3' diaminobenzidine (DAB) histochemical method in four Neotropical galls [16,52,76,77], and were related to the high oxidative stress generated in response to attack by gall-inducing organisms [79]. This accumulation of ROS occurred in the cells of non-galled tissues, which are the mother cells of the gall parenchymatic cortex in Aspidosperma australe and A. spruceanum [75,76].…”
Section: Evidence Of Ros Accumulation and Redox Imbalance During Gallmentioning
confidence: 99%
See 1 more Smart Citation